Guru Pai Dan Perbaikan Mutu Pembelajaran - Abdul Halim Rais (AL-IBNOR, 2023)
Islamic Religious Education is a subject that not only allows students to master various Islamic studies, but also emphasizes more how students are able to master islamic studies as well as be able to practice them in daily life in the midst of society. Thus, Islamic Religious Education does not only emphasize the cognitive aspects alone, but more importantly on the affective and psychomotor aspects. The concept of Islamic religious education is not just taking the cognitive (intelligence) of students by emphasizing the mastery of mere material. But more than that how to give an approach to the affective (attitude) and psychomotor (skills) of the protégé. So that in the students will grow a complete personality in accordance with the teachings of Islam and increase their devotion and faith to Allah Swt. Therefore the role of the teacher is very important in learning Islamic religious education, of course with the competence possessed by the religious teacher.